1966
DOI: 10.1002/jlac.19666910120
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Tuboflavin, 4‐Äthyl‐canthin‐6‐on und Canthin‐6‐on

Abstract: ~ Kondensation von (&)-Tryptophan rnit (+)-khylbernsteinsaureanhydrid fdhrte zu einemGcmisch der beiden Acylaminosauren 2 und 6. Die reinc Saure 2 gab beim Erhitzcn mit einem Gemisch von Polyphosphorsaure, Phosphoroxychlorid und V205 zur Hauptsachc das bereits bekannte 4-khylcanthin-6-on (3). Das daraus bereitetc 4-khylcanthin (5) lieR sich durch Sclcndioxyd in 3 zuriickfiihren. Oxydative Cyclisierung von 6 und nachfolgende Hydrierung des Cyclisationsproduktes gab 5-khyl-4.5-dihydrocanthin-6-on (7), das iiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Up to now several multi‐step syntheses of the alkaloids tuboflavine [11], isotuboflavine [7], norisotuboflavine [7, 12], and of unsubstituted canthin‐4‐one [7] have been published, but none of these offer overall yields higher than 1%. So these total syntheses could only serve as proofs for the structures of the alkaloids, but do not represent efficient approaches to the canthin‐4‐one ring system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now several multi‐step syntheses of the alkaloids tuboflavine [11], isotuboflavine [7], norisotuboflavine [7, 12], and of unsubstituted canthin‐4‐one [7] have been published, but none of these offer overall yields higher than 1%. So these total syntheses could only serve as proofs for the structures of the alkaloids, but do not represent efficient approaches to the canthin‐4‐one ring system.…”
Section: Resultsmentioning
confidence: 99%
“…Recrystallization from CH 2 Cl 2 ‐heptane gave pale yellow needles, mp 294°C (lit. [7, 9, 11]: mp (diethyl ether) 298–300°C, (methanol) 282–284°C, (methanol) 294–296°C); IR: 1633, 1607, 1496, 1428, 1289, 1220 cm −1 ; 1 H NMR (deuteriochloroform) δ 8.92 (d, 1H, J = 4.7 Hz, 2‐H), 8.08 (d, 1H, J = 7.7 Hz, 11‐H), 7.99 (d, 1H, J = 4.7 Hz, 1‐H), 7.83 (d, 1H, J = 8.4 Hz, 8‐H), 7.60 (m, 1H, 9‐H), 7.42 (dd, 1H, J = 7.5, 7.6 Hz, 10‐H), 6.35 (s, 1H, 5‐H), 2.87 (s, 3H, CH 3 ); 13 C NMR (DMSO‐d 6 ) δ 178.8 (CO), 147.0 (C‐6), 146.7 (C‐2), 140.1 (C‐7a), 138.5 (C‐3a), 135.4 (C‐11c), 133.4 (C‐11b), 130.9 (C‐9), 125.4 (C‐11a), 124.6 (C‐10), 123.7 (C‐11), 118.2 (C‐1), 117.6 (C‐5), 114.4 (C‐8), 21.3 (CH 3 ); ms (EI) m/z 234 (M + , 100), 217 (15), 195 (25), 168 (62), 139 (22) and 113 (27); Anal. Calcd.…”
Section: Methodsmentioning
confidence: 99%
“…The use of the Bischer-Napieralski reaction to synthesize canthin-6-one alkaloids was first reported in 1966 [27], and Soriano-Agaton et al reported a more recent synthesis in 2005 (Scheme 3) [2]. The overall yield of canthin-6-one in the later synthesis was increased to 76.83% in four steps by Soriano-Agaton.…”
Section: Chemistrymentioning
confidence: 99%
“…Based on the biosynthetic line of canthin-6-one alkaloids, the infractine-functionalized and nanoparticle-supported biomimetic synthesis of canthin-6-one was accomplished [26]. The first total synthesis of canthin-6-one ( 1 ), which was achieved with a poor overall yield via a classic Bischer-Napieralski method, was reported in 1966 [27]. In 2013, Hollis Showalter et al reviewed the synthetic approaches to canthin-6-ones and their ring-truncated congeners [28], their review including almost all reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…We three were hard working and became good friends, also outside the university. My first research place was in Lab 17, [14] close to the bench of Hans Jürgen Rosenkranz, who had started his PhD work on the synthesis of tuboflavine and analogues already end of 1963 [15] and where Janos had his bench. Georg, Janos, and I, we formed a sort of mechanistic troika, with new ideas every day and endless discussions, since the Woodward-Hoffmann rules had been published just that summer in J. Amer.…”
Section: Back In Zurichmentioning
confidence: 99%